2012
DOI: 10.1159/000337347
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Ranibizumab versus Thermal Laser Photocoagulation in the Treatment of Extrafoveal Classic Choroidal Neovascularization Secondary to Age-Related Macular Degeneration

Abstract: Background: To compare the efficacy of thermal laser photocoagulation versus intravitreal ranibizumab for the treatment of extrafoveal classic choroidal neovascularization (CNV) secondary to age-related macular degeneration (AMD). Methods: We conducted a retrospective study on 24 eyes with extrafoveal classic CNV secondary to AMD, treated either with thermal laser photocoagulation (group 1) or with intravitreal ranibizumab (group 2). Visual acuity, number of injections/sessions and recurrence rate were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 58 publications
1
8
0
2
Order By: Relevance
“…Authors described the maintenance of a good BCVA during the whole follow-up. 32 In our study, we found 80.6% of recurrences at 1-year follow-up and 100% at 2-year follow-up.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Authors described the maintenance of a good BCVA during the whole follow-up. 32 In our study, we found 80.6% of recurrences at 1-year follow-up and 100% at 2-year follow-up.…”
Section: Discussionsupporting
confidence: 53%
“…29 The efficacy of intravitreal ranibizumab and bevacizumab in the treatment of nonsubfoveal CNV was investigated only in three small case series with a short follow-up. [30][31][32] An unequivocal anti-vascular endothelial growth factor drugs regimen has not been proven for the treatment of retinal angiomatous proliferation (RAP) because of the paucity of long-term data and the lack of clinical trials, 33,34 ranibizumab and bevacizumab, either alone or combined with photodynamic therapy, achieved good results in terms of functional and anatomical features. [35][36][37][38][39][40][41][42] Nevertheless till now, differences in results because of a different location have not been taken into consideration.…”
mentioning
confidence: 99%
“…Intravitreal injection of anti-vascular endothelial growth factor (VEGF) is an effective treatment for exudative age-related macular degeneration (AMD) [ 1 2 3 4 ]. Recent reports have demonstrated that anti-VEGF therapy is also effective in treating extrafoveal exudative AMD [ 5 6 ], and one study demonstrated that the treatment outcome of anti-VEGF therapy was superior to that of laser photocoagulation in extrafoveal lesions [ 6 ].…”
mentioning
confidence: 99%
“…Wachstumsfaktor "vascular endothelial growth factor" (VEGF) multimodaler geworden, sodass die Laserbehandlung bei einigen wichtigen Erkrankungsbildern, wie z. B. bei choroidalen Neovaskularisationen der Makula, ihren Stellenwert verloren hat [7,8].…”
Section: Wann Wird Heute Noch Gelasert? Indications For Retinal Laserunclassified